Investigating a Derecho in a Future Warmer Climate - Lasher-Trapp, Sonia; Orendorf, Sophie A.; Trapp, Robert J. (Bulletin of the American Meteorological Society, 2023)
Derechos are extensive swaths of damaging winds produced by some long-lived, widespread mesoscale convective systems. Little research has been conducted concerning how derecho mechanisms might change in a future, warmer climate. In this study, the pseudo–global warming method is utilized to evaluate how the 10 August 2020 midwestern U.S. derecho, the costliest thunderstorm event in U.S. history to date, might differ if it instead occurred in a warmer climate at the end of this century. The 10 August derecho event is first simulated in its observed environment, and then resimulated in environments altered according to projections from different climate models using a high-emissions climate change scenario. Results suggest that near the end of this century, a similar derecho event may not necessarily have more intense winds but could possibly impact a geographical area 50% to 100% larger. The physical chain of events leading to this greater geographical impact result from the derecho winds beginning earlier in the storm lifetime, due to increased precipitation combined with decreased relative humidity right above the ground, and derecho winds extending northward due to a strengthening of the parent storm from increased instability there. All these factors enhance the area of evaporative cooling and thus the cold pool, which in turn extends the area covered by the rear-inflow jet within the storm, the likely main mechanism for most of the damaging winds at the ground in the historical event. More study of other cases is required to evaluate the generality of this result.